Concept of Health Across Different Ages: A Review - Talreja, Shreya; Tiwari, Dr. Shashank (Asian Journal of Pharmaceutical Research and Development, 2021)
Health is not just absence of disease rather health is a holistic well being in terms of physical, psychological as well as environmental health of an individual. At different stages of live human beings attach different meaning to the concept of health. In childhood development of the child is central to the concept of health. In this paper perception and issues of health at different stages of human life are discussed. In human life childhood is all about timely and proper development of the child physically, mentally, emotionally and socially to develop the child into a responsible adult. Children who face developmental issues or health issues receive specific kind of interventions which are absolutely needed for their condition. These interventions are different from that of adults like small dosage of medicine to children or different intervention of therapy in children than in adults. Similarly in adults the perception of health and issues of health also differ from other stages. The interventions too at this stage are highly specific to the condition those are trying to cure. Lastly in old age there is different perception of health, old aged people generally experience many physical ailments like arthritis, hearing impairment and heart related issues etc. care of these people must be done catering to their specific needs. Taking care of old people is different from that of an adult or a child. Older people need extra attention because in old age they usually are dependent on someone’s care.